Community-Centered Journalism 2020
DOI: 10.5622/illinois/9780252043307.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Stories with Solutions Journalism

Abstract: Chapter One introduces an example of how communication infrastructure theory can be used to diagnose the communication health of communities and to design an intervention in response. It also explores the role of place in influencing relationships between actors in local storytelling networks—in this case focusing on majority Black and Latinx communities in South Los Angeles that have historically been stigmatized by negative news representations. The chapter outlines a research-based intervention that sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Moreover, as constructivist studies of trust have emphasized, to trust or distrust news is more than a matter of reliable facts. Trust also depends on more affective, intuitive, and experience-based perceptions of inclusion, integrity, and responsibility (Coleman et al 2009; Schmidt et al 2019; Wenzel 2020). While the impact of such “gut feelings” may be more difficult to examine in research than the application of skills taught in media education, we argue that taking users' tacit knowledge into account is crucial to understand the decisions they make about trust when navigating news.…”
Section: Trust and News Usementioning
confidence: 99%
“…Moreover, as constructivist studies of trust have emphasized, to trust or distrust news is more than a matter of reliable facts. Trust also depends on more affective, intuitive, and experience-based perceptions of inclusion, integrity, and responsibility (Coleman et al 2009; Schmidt et al 2019; Wenzel 2020). While the impact of such “gut feelings” may be more difficult to examine in research than the application of skills taught in media education, we argue that taking users' tacit knowledge into account is crucial to understand the decisions they make about trust when navigating news.…”
Section: Trust and News Usementioning
confidence: 99%
“…partners, they did not directly verify the extent these partners reflected the needs, interests, and assets of these communities. By starting with known-to-them influencers and outlets, they missed an opportunity to build more direct relationships and two-way feedback loops with a broader group of community members, for example by following a “community-centered process model” where formative research informs workshops or other forums where community stakeholders and journalists co-design interventions (Wenzel, 2020). 39 Some of their future plans to organize community events in conjunction with the project could potentially move them in this direction and allow them to begin to build relationships beyond existing WHYY audiences and N.I.C.E.…”
Section: A (Limited) Intervention Into Local Storytelling Networkmentioning
confidence: 99%
“…When these links are strong, researchers have found that storytelling networks tend to have higher levels of civic engagement and community belonging (Kim and Ball-Rokeach, 2006). But researchers have also found that these links can be disrupted by multiple factors including ethnicity, language, or the circulation of exclusively negative stories (Broad et al, 2014; Chen et al, 2013)—or when objectivity norms discourage journalists from collaborating with community organizations or other community stakeholders (Wenzel, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further, while trust is often conceptualized as an external response to journalism, reporters and editors are constantly responsive to the trust/distrust conditions in which they operate, and their work is shaped in negotiation with these conditions. Scholars have been exploring for some time how reporting is affected and modified in response to trust/distrust (Wenzel, 2020; Wenzel et al, 2020; Zahay et al, 2020). There is increasing evidence that editors are modifying how stories are presented as a result of distrust: For example, in the past few years it has become a much more common practice to publish explainers that detail how stories were produced, and editors have also been publishing more raw documents and primary materials as part of major stories with the purpose of increasing trust levels (Mor and Reich, 2018).…”
Section: The Functions Of Trust In the Life Cycle Of Newsmentioning
confidence: 99%